Foot of the Wave Analysis for Mechanistic Elucidation and Benchmarking Applications in Molecular Water Oxidation Catalysis. Issue 23 (15th November 2016) - Matheu, Roc; Neudeck, Sven; Meyer, Franc; Sala, Xavier; Llobet, Antoni
Abstract: The description of the foot of the wave analysis (FOWA) applied to the electrocatalytic oxidation of water to dioxygen is reported for cases where the rate determining step is first order and second order with regard to catalyst concentration, coinciding mechanistically with the so‐called water nucleophilic attack (WNA) and the interaction of two M−O units (I2M, where M represents the metal center of the catalyst), respectively. The newly adapted equations are applied to a range of relevant molecular catalysts, both in homogeneous and heterogeneous phase, and the kinetic parameters are determined, including apparent rate constants and turnover frequencies. In this respect, the application of FOWA at different catalyst concentrations allows elucidation of the reaction mechanism that operates in each case. In addition, catalytic Tafel plots are used for assessing the performance of several molecular water oxidation catalysts (WOCs) as a function of overpotential under analogous conditions, and thus can be used for benchmarking purposes. This analysis was carried out earlier for oxide‐based WOCs; however, this is the first report using molecular WOCs. Abstract : Analyze this ! The electrochemical methodology of the foot of the wave analysis is adapted to electrochemical water oxidation, allowing for the calculation of the catalytic water oxidation apparent rate constants in a very simple and reliable manner, leading to the distinction between the catalytic mechanisms. The catalytic Tafel plots are also used for easily and graphically comparing water oxidation catalysts under identical conditions.